Revisiting the Gandhi–Ambedkar Debates over 'Caste': The Multiple Resonances of Varņa. (January 2019) - Barua, Ankur
While Gandhi and Ambedkar hold similar standpoints on the relation between religious orderings of the world and shapes of social existence, they sharply diverge, on certain occasions, regarding the question of what the crucial terms 'caste' and varņa refer to, so that they often seem to be talking past each other. Gandhi sought to cut through various traditional forms of Hindu socio-religious practices and develop a Hinduism which is grounded in the values of universal peace, love and benevolence. Ambedkar too rejected aspects of familiar historical varieties of Buddhism and configured a new vehicle whose goals were to be more specifically material than spiritual. However, while both Gandhi and Ambedkar thus sought to uncover the revitalizing impulses of religious ideals, they operated with different imaginations of the type of polity that would emerge from this social reconstruction. For Gandhi, the reinvigorated socio-religious whole would be structured by an ideal notion of varņa in which there would be no enmity among the interdependent units. For Ambedkar, in contrast, the vocabulary of varņa was irredeemably corrupted through its enmeshment in millennia-old structures of hierarchy, so that its employment would not generate sufficient momentum to break through entrenched systems of oppression.